Navigating the Digital Frontier: A Literature Review on Business Digitalization - Benga, Btissam; Elhamma, Azzouz (European Scientific Journal, ESJ, 2024)
The rise of digital technology has compelled organizations to undergo significant changes or, at the very least, reassess their operational strategies. Many major corporations have poured significant financial resources into what is commonly referred to as "Digitalization." Digital transformation has become an imperative for businesses that want to survive and thrive in an ever-changing world. Faced with the rise of digital technology, organizations must imperatively adapt their processes, products and services to meet new customer expectations and remain competitive. Digitalization, the integration of digital technologies into various aspects of life and business, has revolutionized industries across the globe. Key components of this transformation include big data, artificial intelligence (AI), cloud computing, Internet of Things (IoT), and machine learning (ML) ,but even if Digitalization offers numerous benefits, including increased efficiency, innovation, and improved customer experiences, it also presents challenges such as security risks, the digital divide, technological dependency, and ethical considerations. Addressing these limitations is crucial to harnessing the full potential of digital technologies for positive societal impact. The objective of our article is to present a literature review on digitalization and provides an overview of the notable constraints and obstacles associated with digitalization and its advancement. It delves into the challenges related to the demand for digital resources, as well as the efficient and effective utilization thereof.